Cálculo de coeficiente de conversão de dose em tomossíntese mamária digital utilizando simulador antropomórfico adulto feminino e o código MCNPX - Alves, Marcos Santos (2017)
The breast tomosynthesis is appearing in several studies that aim to investigate most appropriate parameters to obtaining images of high quality with dose values of ionizing radiation within the limits imposed for digital mammography. The parameters are related to an angular range limited used in examinations, the number of projections, the X-rays beam energies, and the reconstruction of projections, using specific algorithm, mainly. The advantage of tomosynthesis while a new mammographic technology in relation to the other techniques that employ X-rays is its potential to reduced overlap effect of breast tissue. The contribution of variation of the angle of the beams on the dose in breast examined, due to a change in the geometry used in the examination, should be investigated. To determine the impact that this variation has on the dose in the breast and in other organs and tissues of the human body, an important tool is the Computational Simulation by Monte Carlo. The main proposal of this work was to use the code of Monte Carlo N-Particle eXtended (MCNPX) to study absorbed doses in breast and other organs of the patient during the examination of digital tomosynthesis mammary glands. For this reason, it was used an anthropomorphic female adult phantom with representation of the body, tissues and internal structures and realistic adult patient incorporated in a scenario of radiation from a commercial model of equipment of each. The values of absorbed doses found with the AGMS-M tomosynthesis meter were lower than in digital mammography, the differences between tomosynthesis and mammography were 12.3% using 24 kVp, 10.74% for 28 kVp and 11.21% for 30 kVp. Comparing the experimental and that found in the simulation, the values of the absorbed doses had a smaller difference verified to 24 kVp, of 3.3% and a greater difference to 28 kVp, of 6.2%. The results obtained for the colon and brain have presented relative error (R) above 10% due to the occurrence of natural shielding and distance of these components of the primary beam of radiation. The CCs of equivalent dose in this study show that the estimated dose in the simulator anthropomorphic adult female is much greater in each of which in mammography, because the configuration of the acquisition of different geometry between digital mammography and tomosynthesis, and the sweep time which is higher in each.